2003
DOI: 10.1021/ja027765m
|View full text |Cite
|
Sign up to set email alerts
|

Neomycin Binding to Watson−Hoogsteen (W−H) DNA Triplex Groove:  A Model

Abstract: Neomycin is the most effective aminoglycoside (groove binder) in stabilizing a DNA triple helix. It stabilizes TAT, as well as mixed base DNA triplexes, better than known DNA minor groove binders (which usually destabilize the triplex) and polyamines. Neomycin selectively stabilizes the triplex (in the presence of salt), without any effect on the DNA duplex. (1) Triplex stabilization by neomycin is salt dependent (increased KCl and MgCl(2) concentrations decrease neomycin's effectiveness, at a fixed drug conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 64 publications
(106 reference statements)
4
89
0
Order By: Relevance
“…Neomycin selectively stabilizes DNA triplex without affecting the duplex [113][114][115][116]. Increasing the molar ratios of neomycin from 0-25 µM, r db (ratio drug [neomycin]/base triplet)=1.67, increases the triplex melting point by nearly 25°C, whereas the duplex is virtually unaffected (Fig.…”
Section: Effect Of Neomycin On a Polynucleotide Triplexmentioning
confidence: 96%
See 1 more Smart Citation
“…Neomycin selectively stabilizes DNA triplex without affecting the duplex [113][114][115][116]. Increasing the molar ratios of neomycin from 0-25 µM, r db (ratio drug [neomycin]/base triplet)=1.67, increases the triplex melting point by nearly 25°C, whereas the duplex is virtually unaffected (Fig.…”
Section: Effect Of Neomycin On a Polynucleotide Triplexmentioning
confidence: 96%
“…Previous studies of neomycin have shown that it has a marked preference for binding to the larger Watson-Hoogsteen (W-H) groove of the triplex [116]. Ring I/II amino groups and Ring IV amines were proposed to be involved in the recognition process.…”
Section: Cd/molecular Modelingmentioning
confidence: 99%
“…There is extensive evidence describing the ability of aminoglycosides (e.g. neomycin) to bind both duplex and triplex forms of DNA, in addition to quadruplex structures, DNA:RNA hybrids, and to some extent, single-stranded nucleic acids [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Some exceptions have been reported. The Crick-Hoogsteen groove is very narrow, but the Watson-Hoogsteen groove may accommodate the binding of some ligands, like neomycin [124]. It has also been reported that DAPI, which is usually a groove binder, may intercalate into some triple helices [125].…”
Section: Structural Featuresmentioning
confidence: 99%
“…A rationale has been provided for the differential effects of 2,6-, 2,7-and 1,4-disubstituted anthraquinone derivatives on triplex stabilization [127,128]. Molecular modelling has also suggested that neomycin displays a good charge and shape complementarity with the Watson-Hoogsteen groove of triplexes [124,129].…”
Section: Structural Featuresmentioning
confidence: 99%